Continuous-Time Signals - Shmaliy, Yuriy (Signals and Communication Technology,, 2006)
Continuous-Time Signals is an extended description of continuous-time signals related to the course of Signals and Systems. As a time-varying process of any physical state of any object, which serves for representation, detection, and transmission of messages, a modern electrical signal possesses, in applications, many specific properties. To make possible for readers to deal with signals free, the book systematically covers major principle foundations of the signals theory. The representation of signals in the frequency domain (by Fourier transform) is considered with strong emphasis on how the spectral density of a single waveform becomes that of its burst and then the spectrum of its train. Different kinds of amplitude and angular modulations are analyzed noticing a consistency between the spectra of modulating and modulated signals. The energy and power presentation of signals is given along with their correlation properties. Finally, presenting the bandlimited and analytic signals, the book elucidates the methods of their description, transformation (by Hilbert transform), and sampling.